The Historical Development and Adaptation of Open Universities in Turkish Context - Aras Bozkurt (Athabasca University Press, 2019)
Open and Distance Learning (ODL) has a long history, one marked by the emergence of open universities, which was a critical development in the ecology of openness. Open universities have taken on significant local and global roles within the framework of meeting the needs of their respective regions of influence, and as such, their roles have evolved over time. Against this background, the purpose of this research is to explore the open university phenomenon by examining the case of Anadolu University in Turkey, a mega university that has transformed into what is now a giga university. More specifically, the research first looks at openness in education and how the concept itself has led to the emergence of open universities, before turning attention to Anadolu University, which is a dual-mode, state university with around 3 million enrolled students. Other issues that are addressed as part of this research include the rise of ODL and how it positioned itself within Turkish higher education; the historical development of Anadolu University and its massiveness, in terms of student numbers and services provided; local and global ODL practices; learner profiles, learning materials and spaces; exams and assessment and evaluation processes; learner support services, and Anadolu University’s contribution, as an open university, to the field of ODL. The research shows that as an open university, Anadolu University has narrowed the information gap and digital divide, has enhanced equality of opportunity in education, and has provided lifelong learning opportunities. More importantly, as an institution that has gone beyond the conventional understanding of an open university, Anadolu University serves as a catalyst of change and innovation in its emergence as a role model for other higher education institutions. The following recommendations were able to be developed from the examinations of this study: (1) develop a definition of “openness” based on the changing paradigms of the 21st century and online learning, (2) enter into national and international collaborations between open universities, (3) adopt culturally relevant open pedagogies, (4) develop and design heutagogy-based curricula, and (5) unbundle ODL services in mega and giga universities.